Regulating Ag Wettability via Modulating Surface Stoichiometry of ZnO Substrates for Flexible Electronics. (24th June 2021) - Lee, Taehyeong; Kim, Daekyun; Suk, Myung Eun; Bang, Geumhyuck; Choi, Jiyun; Bae, Jong‐Seong; Yoon, Jang‐Hee; Moon, Won Jin; Choi, Dooho
Abstract: A novel and highly efficient methodology to regulate (enhance or suppress) the Volmer–Weber 3D growth mode of ultra‐thin (<10 nm) Ag layers by modulating the surface stoichiometry of ZnO substrates prior to Ag deposition is presented. Relative to pristine ZnO layers, oxygen‐deficient surface states formed by preferential removal of surface oxygen atoms remarkably improve Ag layer wettability, whereas oxygen‐excessive surface states formed by oxygen atom incorporation strongly facilitate Ag agglomeration. The dissimilar nucleation and coalescence dynamics are elucidated via combined molecular dynamics and force‐bias Monte Carlo simulations. The improved wettability results in significantly lower sheet resistance in the ultra‐thin (6–10 nm) Ag layers, for example, 6.03 Ωsq −1 at 8 nm, than the previously reported values from numerous other approaches in the equal thickness range. When this unique methodology is applied to ZnO/Ag/ZnO transparent electrodes, simultaneous improvement in electrical conductivity and visible transparency is realized, with a resultant Haacke figure of merit value of 0.139 Ω −1 that is >50% higher than the best reported value for an identically structured electrode. We select transparent heating devices as a model system to confirm that the superior optoelectronic properties are highly sustainable under simultaneous and severe electrical, mechanical, and thermal stresses. Abstract : The Volmer–Weber 3D growth mode of ultra‐thin Ag layers can be efficiently regulated by modulating the surface stoichiometry of ZnO substrates prior to Ag deposition. When the methodology is applied to ZnO/Ag/ZnO transparent electrodes, a Haacke figure of merit value of 0.139 Ω −1 is achieved, which is >50% higher than the best reported value for an identically structured electrode.